Pengaruh kualitas pelayanan, lokasi dan persepsi harga terhadap kepuasan pelanggan di Hotel The Grove Suites - Putri Aliffa, Sara; Reza Ruliarto, Heidi (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This study's purpose was to analyze the effect of service quality, location, and perceived cost on customer satisfaction at The Grove Suites Hotel. This study's participants were visitors of The Grove Suites Hotel in June 2022. Purposive sampling was employed to pick one hundred responses. Respondents who have visited and stayed at The Grove Suites Hotel at least twice are the deliberate sampling criteria. Collecting data using a questionnaire utilizing a Likert scale with 5 (five) potential replies. This analytical approach involves multiple regression using SPSS 25. The technique for assessing data utilizes the conventional assumption tests (Normality Test, Heteroscedasticity Test, Multicollinearity Test, and Linearity Test). The model is determined by hypothesis testing utilizing the F test, T test, correlation test, and coefficient of determination (R2). The results indicated that the service quality variable partially had a significant effect on customer satisfaction, the location variable had a significant effect on customer satisfaction, and the price perception variable had a significant effect on customer satisfaction. So, it can be concluded that, the variables of product service quality, location, and price perception all affect customer satisfaction simultaneously.